A combined, bioidentical, oral, 17β-estradiol and progesterone capsule for the treatment of moderate to severe vasomotor symptoms due to menopause. Issue 8 (3rd August 2019) - Archer, David F.; Bernick, Brian A.; Mirkin, Sebastian
ABSTRACT: Introduction : Many women seek treatment to alleviate menopausal vasomotor symptoms (VMS). Numerous women use combination compounded hormone therapy (CHT) to achieve the benefits of estrogen/progesterone for endometrial protection. TX-001HR is a combination of bioidentical 17β-estradiol (E2) and progesterone (P4) in a single capsule designed for continuous daily use to treat moderate to severe VMS. Areas covered : This drug profile describes the efficacy and safety of 4 doses of this E2/P4 (mg/mg: 1/100, 0.5/100, 0.5/50, 0.25/50) for treating moderate to severe VMS in menopausal woman with a uterus. Expert opinion : In REPLENISH (NCT01942668), the two highest doses of TX-001HR significantly reduced VMS frequency and severity at 4 and 12 weeks versus placebo (co-primary endpoints); all doses met the primary endpoint of endometrial safety. Rates of amenorrhea were high and improved over time; the Menopause Quality of Life and Medical Outcomes Study-Sleep instruments improved with E2/P4. TX-001HR was well tolerated and had no clinically significant impact on vital signs, metabolic or coagulation parameters, or breast safety. The combination bioidentical E2/P4 capsule (1 mg/100 mg dose was FDA-approved as Bijuva in October 2018) may provide a safe, effective, rigorously studied alternative for women with a uterus who prefer CHT for relief of VMS.